Using a Digital Flashcard Application to Improve Vocabulary Mastery among Elementary EFL Learners - Haryati Haryati; Muhammad Zacky Al Faraby (Universitas Hamzanwadi, 2025)
Vocabulary instruction at the elementary level in Indonesia often remains decontextualized and insufficiently aligned with learners’ cognitive and affective needs, resulting in low engagement and limited vocabulary comprehension. To address this issue, this study investigated the effectiveness of the Englishcard digital flashcard application in enhancing fourth-grade students’ vocabulary mastery. It explored students’ perspectives on its use in vocabulary learning at a private primary school. This study employed a quasi-experimental design with a mixed-methods approach. Forty-four fourth-grade students were selected through purposive sampling and divided into an experimental group (n = 20) that received vocabulary instruction using the Englishcard application and a control group (n = 20) that received conventional instruction using English textbooks. The treatment was conducted over eight instructional meetings. Quantitative data were collected through pre- and post-tests and analyzed using SPSS 26, including tests of normality, homogeneity, and independent-samples t-tests. Qualitative data were obtained through open-ended interviews with students in the experimental group and analyzed using content analysis to examine perceived opportunities and challenges of the application. The quantitative findings revealed a significant improvement in vocabulary mastery among students taught using the Englishcard application, with a Sig. (2-tailed) value of 0.000 (< 0.05), indicating that the application was practical in improving students’ vocabulary achievement. Qualitative findings further showed that students perceived Englishcard as supporting personalized learning, engagement, flexible access, and diverse learning styles. Nevertheless, challenges related to repetitive activities, motivation, and technical barriers, such as internet connectivity, were also identified. the findings suggest that the Englishcard application is an effective supplementary tool for vocabulary instruction when supported by appropriate teacher guidance and infrastructure, offering pedagogical implications for elementary EFL vocabulary learning in similar contexts.